Comparative Assessment of Phenolic Bioaccessibility from 100% Grape Juice and Whole Grapes. (29th May 2020) - Mohamedshah, Zulfiqar; Chadwick-Corbin, Sydney; Wightman, JoLynne; Ferruzzi, Mario
Abstract: Objectives: Grapes and their 100% juices are rich sources of health promoting phenolics. Juicing of grapes includes contact with phenolic rich seeds and skins that otherwise relies on mastication for phenolic release from fruit. To understand if 100% grape juice can provide a matrix with highly bioaccessible phenolics relative to whole fruit, differences in phenolic content and bioaccessibility from commonly consumed table, Concord (CG) and Niagara (NG) grapes and their 100% juices were compared. Methods: Phenolic content in CG, NG, table grapes, 100% Concord grape juice (CGJ), and 100% Niagara grape juice (NGJ) were assayed by LC-MS prior to subjecting grapes and juices to in vitro digestion to determine phenolic bioaccessibility. Results are expressed as relative and absolute bioaccessible content of individual phenolic species and total phenolics as a sum of anthocyanins (AC), flavan-3-ols (FL3), flavonols (FV), stilbenoids, procyanidins, and phenolic acids (PA). Results: Phenolic compounds were concentrated in CG and NG seeds as FL3 (304.1–390.7 mg/100 g dw). CG skins were rich in AC (1050.5 mg/100 g dw) and FV (80.8 mg/100 g dw). Grape product form had a significant impact on content ( P < 0.01), relative bioaccessibility, and absolute bioaccessibility ( P < 0.01). CG had a higher total phenolic content (21.9–50.7 mg/100 g fw) compared to CGJ (5.8 mg/100 g fw), though NG (4.9–10.8 mg/100 g fw) was similar in phenolic content as NGJ (9.4–10.8 mg/100 g fw). Absolute bioaccessibility of CGJ total phenolics (5.2 mg/100 g fw) was similar to CG (2.6–9.6 mg/100 g fw), while NGJ (5.1–5.7 mg/100 g fw) had higher bioaccessible phenolic content than NG (0.8–1.1 mg/100 g fw). Differences in initial content and bioaccessible fractions were driven by higher relative bioaccessibility of AC in CGJ (86–135%) compared to CG (14–39%) and FL3/PA in CGJ/NGJ (48–101; 39–85%) compared to CG/NG (0–3; 9–67%). Comparisons between juices and table grapes followed similar trends. Conclusions: A greater fraction of grape skin and seed derived PA, AC, and FL3 are extracted through juicing and made bioaccessible relative to whole fruit. 100% juice may provide an improved matrix for delivery of grape phenolics and despite some processing losses, whole fruit and juice are similar in overall phenolic delivery to consumers. Funding Sources: Welch Foods Inc.